Oral Agreements In The Perspective Of Pacta Sunt Servanda In Legal Certainty - triana, yeni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The purpose of this study is to analyze the problem of breaking a promise in an oral agreement, one of the parties, does not carry out what has been agreed upon, and causes losses, resulting in a conflict, and is sued by the district court. The problem in this study is how the court judge's consideration of the oral agreement, and the legal consequences. This research method uses a normative juridical approach, examines jurisprudence, the existence of cases that have been decided by the court. The legal theory in this study is the agreement theory, guided by the principles in the agreement, then the legal terms of a contract, and the types of agreements based on the Civil Code. The results of this study are as learning and utilization as student lecture material, and useful for the parties in an oral agreement. This output achievement is an article that will be published in a journal, so that it can be used by the public.